Logjams and Channel Morphology Influence Sediment Storage, Transformation of Organic Matter, and Carbon Storage Within Mountain Stream Corridors. Issue 5 (11th May 2021) - Sutfin, Nicholas A.; Wohl, Ellen; Fegel, Timothy; Day, Natalie; Lynch, Laurel
Abstract: The flow of organic matter (OM) along rivers and retention within floodplains contributes significantly to terrestrial carbon storage and ecosystem function. The storage and cycling of OM largely depend upon hydrogeomorphic characteristics of streams and valleys, including channel geometry and the connectivity of water across and within the floodplain. To examine the role of river morphology on carbon dynamics in mountain streams, we (a) quantify organic carbon (OC) storage in fine sediment, litter, and wood along 24 forested gravel‐bed stream reaches in the Rocky Mountains of CO, USA, (b) examine morphological factors that regulate sediment and OC storage (e.g., channel width, slope, logjams), and (c) utilize fluorescence spectroscopy to examine how the composition of fluorescent dissolved OM in surface water and floodplain fine sediment are influenced by channel morphology. Multivariate regression of the study reaches, which have varying degrees of confinement, slope, and elevation, indicates that OC storage per area is higher in less confined valleys, in lower gradient stream reaches, and at higher elevations. Within unconfined valleys, limited storage of fine sediment and greater microbial transformation of OM in multithread channel reaches decreases OC storage per area (252 ± 39 Mg C ha −1 ) relative to single‐thread channel reaches (346 ± 177 Mg C ha −1 ). Positive feedbacks between channel morphology and persistent channel‐spanning logjams that divert flow into multiple channels may limit the aggradation of floodplain fine sediment. Although multithread stream reaches are less effective OC reservoirs, they are hotspots for OM decomposition and provide critical resources to downstream food webs. Plain Language Summary: Organic matter, in the form of byproducts of plants, insects, and microbes, is a critical component of healthy riverine ecosystems and contributes to carbon storage, which reduces carbon dioxide release to the atmosphere. To examine how the shapes of river channels and valleys influenced organic matter storage, we (a) surveyed 24 streams in the Colorado Rocky Mountains and collected soil samples to estimate carbon storage, (b) related differences in carbon storage to river morphology, and (c) examined how channel geometry influenced the molecular composition of dissolved organic matter. We found that carbon storage per area is higher in wider valleys, in lower gradient streams, and at higher elevations. Within wide valleys, streams with a single channel of flow stored more sediment and carbon than streams with numerous channels of flow. Complex river channels also increased the molecular transformation of carbon by microbial communities. Although complex river features are less efficient reservoirs for organic matter, they increase carbon availability to downstream food webs and play an important role in maintaining healthy ecosystems. Key Points: Less‐confined valleys store relatively more carbon per area in floodplain fine sediment and large wood than more confined valley segments Within wide valleys, channels with single‐thread planforms store more carbon than more complex systems with multiple channels of flow Logjam abundance is linked to microbial transformation of organic matter and shallower fine sediment depth in complex multithread reaches